Assessment of Dumaran National High School Teachers’ Technological-Pedagogical Comspetence in Classroom Instructional Delivery (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study assessed the self-reported technological-pedagogical competence of teachers at Dumaran National High School in classroom instructional delivery. Specifically, it sought to determine the demographic profile of the respondents in terms of age, sex, teaching position, highest educational attainment, and years in teaching; assess their technological-pedagogical competence in terms of Technology Operations and Concepts and Pedagogy; and examine the relationship between their demographic profile and technological-pedagogical competence. The study was framed as a school-based local assessment intended to generate context-specific evidence for professional development planning at Dumaran National High School.The study employed a descriptive-correlational research design using total enumeration. Thirty-three teachers participated in the study, excluding the researcher to avoid bias and conflict of interest. The research instrument was adapted from the National ICT Competency Standards for Teachers and was administered through Google Forms. Frequency counts, percentages, means, Cronbach’s alpha, Fisher’s Exact Test, cross-tabulations, Mann-Whitney U test, and Kruskal-Wallis test were used to analyze the data.Findings revealed that most respondents were 25–30 years old, female, Teacher I, Bachelor’s Degree holders, and had 0–3 years of teaching experience. The teachers demonstrated a moderately high level of self-reported technological-pedagogical competence in both Technology Operations and Concepts and Pedagogy, with an overall grand mean of 2.99. Reliability analysis showed excellent internal consistency for the Technology Operations and Concepts subscale, Pedagogy subscale, and overall instrument. Although the overall competence level was moderately high, lower-rated areas were identified in the use of spreadsheets, online repositories, information and data management, and technology-supported assessment.Using Fisher’s Exact Test, teaching position was found to have a significant association with categorical technological-pedagogical competence, while age, sex, highest educational attainment, and years in teaching were not significant. Follow-up cross-tabulations showed that teaching position was also associated with age and years in teaching, suggesting that the teaching-position result should be interpreted cautiously. Supplementary non-parametric tests using continuous mean scores showed no significant differences according to sex and highest educational attainment, but significant differences were found across age groups, teaching positions, and years-in-teaching groups.The study concluded that teachers at Dumaran National High School generally perceived themselves as moderately competent in integrating technology into classroom instruction. However, continuous school-based professional development is needed, particularly in spreadsheets, digital repositories, data management, and technology-supported assessment. Since the study was conducted in a single school with 33 respondents and relied on self-reported data, the findings should be interpreted as context-specific and not broadly generalizable to all teachers.